Pengaruh Kualitas Pelayanan, Kualitas Produk, dan Promosi Penjualan Terhadap Loyalitas Pelanggan Toko Sepatu Bata Tbk Purbalingga - Basith Ahnaf Jaler M; Herni Justiana Astuti; Suyoto; Arini Hidayah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The objective of this study is to analyze the impact of service quality, product quality, and sales promotion on customer loyalty at Toko Sepatu Bata Tbk Purbalingga. The primary data collection instrument for this study was a questionnaire using a five-point Likert scale. The sample consisted of 110 respondents who were customers of Toko Sepatu Bata Tbk Purbalingga, selected using purposive sampling based on the criterion of having made at least two purchases at the store. Data analysis was conducted using multiple linear regression with SPSS version 25. The results of the study are as follows: 1) Service quality does not have a significant impact on customer loyalty at Toko Sepatu Bata Tbk Purbalingga, 2) Product quality has a positive and significant impact on customer loyalty at Toko Sepatu Bata Tbk Purbalingga, and 3) Sales promotion has a positive and significant impact on customer loyalty at Toko Sepatu Bata Tbk Purbalingga. The implications of this study suggest that Toko Sepatu Bata Tbk Purbalingga should focus on improving product quality and sales promotions to enhance customer loyalty.